2022
DOI: 10.7759/cureus.29568
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Renal Clearance and Hypoalbuminemia-Induced Low Vancomycin Trough Concentrations in Febrile Neutropenic Patients With Hematological Malignancies

Abstract: Introduction: Vancomycin administration in individuals with hematological malignancy or neutropenia is associated with a suboptimal trough concentration. Nonetheless, most studies did not distinguish whether low vancomycin trough concentrations were due to hematological malignancies or neutropenia. This study aimed to determine the association between types of hematological malignancy and febrile neutropenia with low vancomycin concentrations.Methods: The present retrospective chart review study was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Among the most important subjects of recent research is the ability to predict the factors substantially responsible for the failure to achieve the desired vancomycin therapeutic goal in patients with FN. Here, we illustrate in Figure 5 the possible hypothetical mechanism behind such failure based on the findings of the current work and our previous work [ 33 ]. The first and foremost mechanism assumes that FN exerts its effect by causing variation in the PK parameters of vancomycin, which includes (1) a significant increase in vancomycin clearance, which will lead to a marked short in the half-life of the drug.…”
Section: Discussionmentioning
confidence: 89%
“…Among the most important subjects of recent research is the ability to predict the factors substantially responsible for the failure to achieve the desired vancomycin therapeutic goal in patients with FN. Here, we illustrate in Figure 5 the possible hypothetical mechanism behind such failure based on the findings of the current work and our previous work [ 33 ]. The first and foremost mechanism assumes that FN exerts its effect by causing variation in the PK parameters of vancomycin, which includes (1) a significant increase in vancomycin clearance, which will lead to a marked short in the half-life of the drug.…”
Section: Discussionmentioning
confidence: 89%
“…Based on the demographic information presented by Álvarez et al, this approximately corresponds to a CrCl of 200 mL/min. Altough a CrCl of 200 mL/min is generally considered high, this may be explained by augmented renal clearance, which has been associated with febrile neutropenia [ 32 , 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Published data on ARC appear to be limited to adult patients, whereas in recent years, studies have indicated that accelerated clearance of vancomycin exists in children with febrile neutropenia [ 25 ] or sepsis [ 26 ], which may be related to ARC. Studies in adults with a haematologic malignancy showed that febrile neutropenia is associated with low vancomycin concentrations, possibly driven by ARC [ 27 ]. Our study in paediatric patients with haematologic diseases demonstrated a high prevalence of ARC and that neutropenia was a possible influencing factor in the univariate analysis, but serum creatinine level mediated by age was the dominant factor for ARC in the multivariate regression.…”
Section: Discussionmentioning
confidence: 99%